Insulated Hybrid Grid Based on PV System, Battery and Fuel Cell Car—A Case Study - Lucian A. C. Ciochinda; Daniel Fodorean (Engineering Proceedings)
For insulated areas, careful exploitation of the available energy is a must. We are considering a scenario of an off-grid small resort, for which the electrical energy is available only from a photovoltaic (PV) system with a local battery (BAT) storage unit, while a supplementary energy source system could be considered: an electrical propulsion vehicle, i.e., a fuel cell (FC) car. This hybrid system is to be connected to the local three-phase microgrid used to ensure electric energy for in-house needs. This paper investigates through simulations the operability of this small microgrid, while its performances are evaluated to comply with the IEC 61000-2-2 standard in terms of voltage amplitude and current total harmonic distortion (THD).